Lessons Learned from the Operation of Strategic and Technical Advisory Group Under DDC’s Public Health Emergency Management in Response to Flood Crisis 2011 - เหลืองอ่อน วรยา; สงวนวงศ์ นาฏพธู; กิจผาติ รุ่งเรือง; ชุณห์สุทธิวัฒน์ ศุภมิตร (Disease Control Journal, 2012)
During flood crisis in late 2011 in Thailand, Department of Disease Control (DDC) established an incident command system composed of an incident commander and 7 committees to respond to the crisis based on DDC’s roles. One of those committee was the Strategic and Technical Advisory Group (STAG). Its main task was to provide recommendations on policy and strategic aspects of the response including technical guidance on disease prevention and control. After the end of operation in December 2011, the committee reviewed the lessons learned from 2 months of working experiences to provide recommendation to DDC for further improvement on crisis preparedness and response in the future. The review process included focus group discussion, brainstorming and interviews of committee members and concerned authorities were conducted during December 2011-January 2012. Topics under review included situation assessment, mission, execution, administration and logistics, command , communication and coordination (SMEAC). A key conclusion was that STAG achieved its mission. The main products included 19 recommendations and 63 technical guidelines were broadly accepted and appreciated by the DDC administrators, the incident commander, other 6 committees under the incident command system, related government organizations, the media and the public. Improvement of STAG working mechanism and continuous strengthening other components of the incident command system are essential for development of DDC’s Public Health Emergency Management.